High-Fat Diet Feeding Alters Expression of Hepatic Drug-Metabolizing Enzymes in Mice - Ning, Miaoran (Drug Metab Dispos, 2017)
Medical conditions accompanying obesity often require drug therapy, but whether and how obesity alters the expression of drug-metabolizing enzymes and thus drug pharmacokinetics is poorly defined. Previous studies have shown that high-fat diet (HFD) feeding and subsequent obesity in mice lead to altered expression of transcriptional regulators for cytochrome P450 CYP2D6, including hepatocyte nuclear factor 4α (HNF4α, a transcriptional activator of CYP2D6) and small heterodimer partner (SHP, a transcriptional repressor of CYP2D6). The objective of this study was to examine whether diet-induced obesity alters CYP2D6 expression by modulating HNF4α and SHP expression. Male CYP2D6-humanized transgenic (Tg-CYP2D6) mice were fed with HFD or matching control diet for 18 weeks. Hepatic mRNA expression of CYP2D6 decreased to a small extent in the HFD group (by 31%), but the differences in CYP2D6 protein and activity levels in hepatic S9 fractions were found insignificant between the groups. Although hepatic SHP expression did not differ between the groups, HNF4α mRNA and protein levels decreased by ∼30% in the HFD group. Among major mouse endogenous cytochrome P450 genes, Cyp1a2 and Cyp2c37 showed significant decreases in the HFD group, whereas Cyp2e1 expression did not differ between groups. Cyp2b10 and Cyp3a11 expression was higher in the HFD group, with corresponding 2.9-fold increases in hepatic CYP3A activities in HFD-fed mice. Together, these results suggest that obesity has minimal effects on CYP2D6-mediated drug metabolism, although it modulates the expression of mouse endogenous P450s in a gene-specific manner.